INVESTIGATING THE IMPACT OF AUTONOMOUS VEHICLES ON URBAN TRANSPORTATION SYSTEMS AND INFRASTRUCTURE - Haryaman, Adang (Yayasan Kreatif Indonesia Emas, 2024)
Background: Environmental monitoring and disaster management are crucial for mitigating risks and ensuring the sustainability of ecosystems. Wireless Sensor Networks (WSNs) have emerged as transformative tools in collecting real-time data, analyzing environmental parameters, and providing timely alerts.Aims: This paper aims to explore the role, applications, and challenges of WSNs in environmental monitoring and disaster management.Research Method: The research employs a qualitative approach, combining case studies, literature review, and data analysis from recent applications of WSNs in various geographical and environmental contexts.Results and Conclusion: The findings demonstrate that WSNs significantly enhance early warning systems, improve environmental data collection, and facilitate better decision-making in disaster management. Challenges such as energy consumption, scalability, and network security are critical areas for improvement.Contribution: This study provides a comprehensive overview of the practical implications of WSNs and offers recommendations for advancing their deployment in addressing global environmental challenges